Association of body composition with neuroimaging biomarkers and cognitive function; a population-based study of 70-year-oldsResearch in context - Jessica Samuelsson; Anna Marseglia; Ola Wallengren; Olof Lindberg; Caroline Dartora; Nira Cedres; Sara Shams; Silke Kern; Anna Zettergren; Eric Westman; Ingmar Skoog (EBioMedicine)
Summary: Background: A better understanding of body-brain links may provide insights on targets for preventing cognitive decline. The aim was to explore associations of body composition with neuroimaging biomarkers and cognitive function among dementia-free 70-year-olds. Methods: Dual-energy X-ray absorptiometry body composition measures in relation to neuroimaging measures of cortical thickness, hippocampal volume, small vessel disease, predicted brain age, and cognitive performance were explored in a cross-sectional study of 674 dementia-free 70-year-olds from the Swedish Gothenburg H70 Birth Cohort study. Linear or ordinal regression analyses were performed. Findings: Higher quantity of muscle mass was associated with lower predicted brain age (β: −0.31 [95% CI: −0.45, −0.16], p: 0.00013). Those with normal level muscle mass (>7.0 men, >5.5 women kg/height m2) had overall thicker cortex (β: 0.043 [95% CI: 0.023, 0.064], p: 0.00016), thicker cortex in Alzheimer's disease signature regions (β: 0.051 [95% CI: 0.025, 0.076], p: 0.00040), and larger hippocampal volume (β: 111.52 [95% CI: 25.28, 197.75], p: 0.030) compared to those with sarcopenic level muscle mass. Higher accumulation of visceral fat was associated with overall thinner cortex (β: −0.017 [95% CI: −0.028, −0.005], p: 0.024). Faster gait speed and higher handgrip strength were associated with indicators of better brain health. Interpretation: Improving muscle mass fitness and lower visceral fat may be beneficial for brain health. Intervention studies are needed to confirm that targeting body composition can promote healthy brain ageing and reduce the risk of cognitive impairment among older adults. Funding: The Swedish Research Council, Hjärnfonden, and Alzheimerfonden.